The social networks as a communication strategy of the careers offered by the Secretarial Business School - España Chavarría, Carolina (2022)
This research focused on analyzing the use of social network as a communication strategy for the dissemination of the work derived from the careers offered by the “Escuela de Secretariado Profesional” at “Universidad Nacional”, period 2019 Specifically sought: a) diagnosing the actions associated with the use of social networks as a communication strategy for the dissemination of ESP careers, b) determine the communication alternatives that the “Escuela de Secretariado Profesional” has with the use of social networks and c) check the interaction of potential students with the academic unit.The study follows the interpretative research paradigm with a qualitative and descriptive approach. The information collected from students was posible by a three basic dimension instrument that included: personal information, use of devices and social networks, and social networks as a strategy to disseminate the work of the “Escuela de Secretariado Profesional”.Among the most significant findings is the use of social networks by students of both careers, thus generating a profile of use that could eventually serve as an input for the use of social networks in learning environments by the academic and student group.